Homem homem, homem com H e homem-imagem: masculinidades midiáticas nas culturas do consumo - Postinguel, Danilo (2015)
This dissertation is focused on media representations of masculinity produced and transmitted in communication societies and cultures of consumption. Interested us even realize how these representations dialogue with social realities and wider cultural contexts related to symbolic disputes, economic processes and social imaginary negotiating the place and forms of masculinities seen as desirable and/or acceptable by modern western societies. Thus, we focused discussions around notions and representations of masculinity mediated communication dynamics and consumption practices. Our main objective was to analyze how the media masculinities circulating by communication companies and consumption, mobilize different perspectives of masculinity. Our secondary objectives were: a) in addition to drafting a theoretical and conceptual framework (on the concepts of communication and consumption of masculinity and media representation), b) to identify and question as presented in the media these masculinities representations, using theoretical axes featured, c) propose categories of masculinity that could be glimpsed through the analysis of selected advertisements and, d) historically resume construction of masculinity to understand how was the process of crystallization and the gaps to think of masculinities in the plural, in its broad sense. As for the theoretical foundation, we have the contribution of Don Slater, Elisabeth Badinter, Everardo Rocha, Norval Baitello, Pedro Paulo de Oliveira, Rose de Melo Rocha, Socrates Nolasco, Tania Hoff among many other theorists who contribute to think the triad communication, masculinities media and consumption practices. This theoretical bricolage provided build a methodology to seek better contemplate the purpose of this research. In this way, we develop flexible multi-methodological tools, which took centered on the image in the Brazilian socio-cultural context and, globally, in cultures of consumption. Thus, because it is the choice of a contemporary object - new and other masculinities - still under construction in our culture, given its multiple investigative perspective, we chose to analyze the Brazilian advertising communication briefs between the 1960s and 2010. Among the measured results highlight that even see that there was a majority media confirmation of traditional masculinity in the collected corpus, however, this material presented elements that allowed to rethink where to go or what is the restriction that must exist to define what a media representation of masculinity. Given this result, we launched the possibility, from the Reception Studies, to understand how men perceive the offer of masculinities in media communication and advertising and later as the consumption of these imagistic representations reflected in the establishment of consumption and gender identities from what circulates in this sphere of consumption, entitled by us Consumosfera.